Turismo sa Panay... epekto sa tao - Aguilar, Mila D. (Pinoy Tok, 1991)
The effects of tourism on the socio-economic development are discussed. It also covers scenes from the "Ati-Atihan" in Aklan, the "Dinagyang" in Iloilo, and the beaches of Boracay and Guimaras.